Implementation of the Exclusive Breastfeeding Program at the Umban Sari Health Center, Rumbai District, Pekanbaru City: Implementasi Program Asi Eksklusif Di Puskesmas Umban Sari Kecamatan Rumbai Kota Pekanbaru - Cindy Friskhilia Tarigan; Jasrida Yunita; Ahmad Hanafi; M.Dedi Widodo; Siska Mayang Sari (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Exclusive Mother's Milk (ASI) is breast milk that is given to babies from birth to 6 months without providing additional food or replacing it with other foods or drinks, except drugs, vitamins and minerals. Breast milk also contains colostrum which is rich in antibodies, because it contains protein to maintain the baby's immune system and kills germs in high quantities which can also reduce the risk of death in infants. Umban Sari Public Health Center, Rumbai District, is the area with the lowest coverage percentage, which is 48.5%. The problems found at the Umban Sari Health Center related to this exclusive breastfeeding program are HR/Health Personnel, Facilities and Infrastructure, Funding, Coordination, Counseling and Counseling. The purpose of this study was to determine the implementation of the exclusive breastfeeding program at the Umban Sari Health Center, Rumbai District in 2022. This type of research was a qualitative research with descriptive research methods to 8 informants consisting of the Head of the Puskesmas, PJ ASI, 2 Posyandu Cadres, 2 Mothers. Pregnant, Lurah and RW. This research was carried out in April 2022 at the Umban Sari Health Center, Rumbai District, Pekanbaru City in 2022. The results of this study indicate that human resources / health workers are still not optimal because there are still many who have double jobs and there are still no facilities and infrastructure such as diaper changing tables. for babies, breast pumps, etc. and for funding, namely the unavailability of special funds related to the exclusive breastfeeding program, for the coordination itself it has been going well but not specifically for the exclusive breastfeeding program but for all programs and for counseling activities, namely the lack of community participation and support from family during the implementation of this activity and for the outreach activities themselves, which are not carried out routinely every month and community participation is also still low